Long-Acting Cabotegravir Protects Macaques Against Repeated Penile Simian-Human Immunodeficiency Virus Exposures. (4th March 2020) - Dobard, Charles; Makarova, Natalia; Nishiura, Kenji; Dinh, Chuong; Holder, Angela; Sterling, Mara; Lipscomb, Jonathan; Mitchell, James; Deyounks, Frank; Garber, David; Khalil, George; Spreen, William; et al.
Abstract: We used a novel penile simian-human immunodeficiency virus (SHIV) transmission model to investigate whether long-acting cabotegravir (CAB LA) prevents penile SHIV acquisition in macaques. Twenty-two macaques were exposed to SHIV via the foreskin and urethra once weekly for 12 weeks. Of these, 6 received human-equivalent doses of CAB LA, 6 received oral emtricitabine/tenofovir disoproxil fumarate, and 10 were untreated. The efficacy of CAB LA was high (94.4%; 95% confidence interval, 58.2%–99.3%) and similar to that seen with oral emtricitabine/tenofovir disoproxil fumarate (94.0%; 55.1%–99.2%). The high efficacy of CAB LA in the penile transmission model supports extending the clinical advancement of CAB LA preexposure prophylaxis to heterosexual men. Abstract : We used a macaque model of penile simian-human immunodeficiency virus transmission to investigate the efficacy of long-acting cabotegravir (CAB LA) preexposure prophylaxis against penile infection. CAB LA showed high protection, supporting its clinical development for preexposure prophylaxis in heterosexual men.